2005
DOI: 10.1175/jhm450.1
|View full text |Cite
|
Sign up to set email alerts
|

Twentieth-Century Drought in the Conterminous United States

Abstract: Droughts can be characterized by their severity, frequency and duration, and areal extent. Depth–area–duration analysis, widely used to characterize precipitation extremes, provides a basis for the evaluation of drought severity when storm depth is replaced by an appropriate measure of drought severity. Gridded precipitation and temperature data were used to force a physically based macroscale hydrologic model at 1/2° spatial resolution over the continental United States, and construct a drought history from 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
446
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 491 publications
(484 citation statements)
references
References 41 publications
6
446
0
1
Order By: Relevance
“…At large scales, global hydrological models (GHMs) are used to produce runoff time series, which are then used for hydrological drought assessment. At the continental scale, Andreadis et al (2005) investigated runoff drought in the United States and Prudhomme et al (2011) studied European runoff drought. Forzieri et al (2014) project for the A1B scenario that future drought in streamflow will increase in many European regions, except for North and Northeast Europe.…”
Section: N Wanders and H A J Van Lanen: Future Discharge Droughtmentioning
confidence: 99%
“…At large scales, global hydrological models (GHMs) are used to produce runoff time series, which are then used for hydrological drought assessment. At the continental scale, Andreadis et al (2005) investigated runoff drought in the United States and Prudhomme et al (2011) studied European runoff drought. Forzieri et al (2014) project for the A1B scenario that future drought in streamflow will increase in many European regions, except for North and Northeast Europe.…”
Section: N Wanders and H A J Van Lanen: Future Discharge Droughtmentioning
confidence: 99%
“…In light of these difficulties, this paper proposes a simple agglomerative technique to identify large-scale coherent space-time drought events. Andreadis et al, (2005) describe a spatial identification procedure in which all pixels that have a soil moisture (or runoff) percentile value below 20% are considered as being under drought. Those pixels are then classified into drought classes using a simple clustering algorithm.…”
Section: Feature Extractionmentioning
confidence: 99%
“…However, low river flows (streamflow droughts) must also be considered, because many regions are irrigated with river water. Andreadis et al (2005) used a land surface model (LSM) driven by historical atmospheric data on a 1/2° grid to estimate water budget in the 20th century over the USA and found that the shortage of storages in soil moisture and in runoff were not always coincident in space and time. This study implies that low river flows may not be estimated simply from vertical water and energy balances, such as soil moisture or precipitation minus evapotranspiration.…”
Section: Introductionmentioning
confidence: 99%